2016
DOI: 10.18682/pd.v16i2.593
|View full text |Cite
|
Sign up to set email alerts
|

La empatía en la primera infancia

Abstract: ArtículoMaterial original autorizado para la publicación en la revista Psicodebate. Facultad de Ciencias Sociales. Universidad de Palermo.Recibido 16-06-201616-06- | Aceptado 02-11-2016 Resumen A lo largo de la historia del concepto de empatía se han desarrollado dos posturas para poder explicarla. Por un lado encontramos autores que se posicionan desde una visión cognitiva y, por otro, desde una mirada afectiva. En los últimos tiempos se ha logrado una integración interdisciplinaria de ambas. En este trabajo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
0
3
0
3
Order By: Relevance
“…Besides, our results are consistent with previous studies that have found similar results, in which Personal Distress decreases with age ( Eisenberg et al, 2005 ). Evidence from other studies has indicated that brain areas related to affective empathy, which has been related to emotional contagion and mirror neurons ( López et al, 2014 ), mature more quickly than those for cognitive empathy ( Filippetti et al, 2012 ; Gómez, 2016 ; Zavala et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, our results are consistent with previous studies that have found similar results, in which Personal Distress decreases with age ( Eisenberg et al, 2005 ). Evidence from other studies has indicated that brain areas related to affective empathy, which has been related to emotional contagion and mirror neurons ( López et al, 2014 ), mature more quickly than those for cognitive empathy ( Filippetti et al, 2012 ; Gómez, 2016 ; Zavala et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from other studies has indicated that brain areas related to affective empathy, which has been related to emotional contagion and mirror neurons (López et al, 2014), mature more quickly than those for cognitive empathy (Filippetti et al, 2012;Gómez, 2016;Zavala et al, 2018). Regarding emotional regulation skills, interestingly we found that the Early Adolescents group obtained higher scores in the sub-scale Difficulties engaging in goal-directed behavior of DERS, which suggests that the Early Adolescents group shows low control when negative emotions interfere with effective actions to achieve their goals (Muñoz Martínez et al, 2016).…”
Section: Empathy and Emotional Regulation Level's During The Differen...mentioning
confidence: 99%
“…This dimension is related to the emotional phase of empathy and is correlated to the ontogenic development of a person and to how these factors interact in the development of biological and neuronal fundamentals of empathy [33,34]. This interaction occurs starting from a child's first contact with his surroundings, especially in the mother-child relationship [36,37]. The information discussed could consequently lead us to infer that the CC dimension is not likely to be "taught" with psycho-pedagogical "techniques", as is the case with dimensions related to the cognitive aspect of empathy.…”
Section: Discussionmentioning
confidence: 99%
“…Por ende, es de vital importancia que esta situación convergente se prolongue para el niño en una línea de tiempo, no como un recurso que desprovisto de emociones, sino, por el contrario, como situación que permanece en la memoria del cuerpo, con el propósito de ampliar su rango de comprensión sobre los demás. Según va transcurriendo el desarrollo del niño, la empatía va alcanzando no solo a su primer entorno más cercano, sino a sus pares, y termina con conductas de mayor independencia al haber ya logrado ciertas representaciones mentales (Gómez, 2016).…”
Section: Según Bautista Y Navarro (2011)unclassified